Morphological basics of ovarian tumor histogenesis - F. V. Novikov; I. S. Luneva; E. S. Mishina; M. V. Mnikhovich (Опухоли женской репродуктивной системы)
Researches about the origin of epithelial ovarian tumors (EOT) tell about its conception. In particular, the origin of cells from the secondary mullerian system. Also, in the article we examine a new hypothesis that the EOT originates in the epithelium of the fallopian tube (FT) – their contradictoriness and new conception of “precursor escape” which tries to explain the phenomenon of injuries absence of FT by high-grade serous ovarian carcinoma. Carcinogenesis from the FT represents great opportunities for reassessment of clinical data. Also, the article represents the role of stem cells of the surface epithelium of ovaries and FT in EOT carcinogenesis.